Effects of Switching from Conventional Cigarettes to Combustion-Free Nicotine Delivery Systems (C-FNDS) on Salivary TNF-alpha Levels and Gingival Conditions: A Randomized Controlled Trial - Hanna Adianita; Indra Pribadi; Amaliya (The ASEAN Journal of Military and Preventive Medicine, 2025)
Background: Tobacco smoking is an independent risk factor for periodontitis. Smokers may show impaired inflammatory responses, altered gingival vascular function, and increased salivary tumor necrosis factor-alpha (TNF-alpha). This study evaluated changes in salivary TNF-alpha levels and gingival conditions among smokers who switched from combustible tobacco cigarettes to combustion-free nicotine delivery systems (C-FNDS). Methods: This single-blind, open-label randomized controlled trial with 6-month follow-up was conducted at the Department of Periodontics, Dental and Oral Hospital, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia. Forty smokers were randomized into a C-FNDS switching group and a control group that continued combustible tobacco use. Gingival inflammation was assessed using the Modified Gingival Index (MGI), saliva samples were collected to measure TNF-alpha at baseline, 3 months, and 6 months, and exhaled carbon monoxide (CO) was assessed as a secondary outcome. Results: A total of 40 participants were analyzed. Switching to C-FNDS was associated with a reduction in salivary TNF-alpha levels over 6 months and lower MGI scores compared with continued combustible tobacco smoking. Exhaled CO decreased in the switching group, supporting reduced exposure to combustible tobacco products. Conclusion: Switching from conventional cigarettes to C-FNDS for 6 months was associated with reduced salivary TNF-alpha levels, lower gingival inflammation, and lower exhaled CO levels compared with continued combustible cigarette use.